Hybrid Information Systems for Agriculture: The Case of Cattle Trypanosomiasis in Africa - Mckendrick, Iain J.; Gettinby, George; Gu, Yiqun; Peregrine, Andrew; Revie, Crawford (SAGE Publications, 1994)
Large scale population growth in sub-Saharan Africa makes it imperative to achieve an equivalent increase in food production in this area. It is also important that any increase be sustainable in the long-term, not causing lasting damage to local ecosystems. Recent advances in information technology make the successful diffusion of relevant expertise to farmers a more practical option than ever before. How this might be achieved is described in this paper, which considers the transfer of expertise in the diagnosis, treatment and management of trypanosomiasis in cattle. Using current technology, the combination of different software systems in one integrated hybrid system could allow the delivery of high quality, well focused information to the potential user.